Efeitos de (não) evidência do preconceito linguítico no livro didático de língua portuguesa do ensino fundamental II e seus atravessamentos discursivos contraditórios. - Silva, Aurílio Soares da (2023)
In this work, we focus on two collections of Portuguese language textbooks for middle school, using Discourse Analysis with a Pecheuxtian and Orlandian orientation to highlight the discourses present in these materials regarding linguistic prejudice. To do so, we started from the assumption that linguistic prejudice is established as a discourse/ideological clash, constituted by socio-historical determinations, sedimented in the social imaginary that there are better ways of using language than others, leading to linguistic stratification and, consequently, social exclusion of speakers of stigmatized varieties. Thus, while one of the functions of schooling is to enable the formation of a citizen capable of (re)thinking the social inconsistencies that afflict the society in which he lives, on the other hand, the textbook presents itself as a means of facilitating and facilitating the debate and reflection of these diverse themes within the school environment. Therefore, perceiving the discursive ideology of these materials about linguistic prejudice is a means of understanding how education and, more specifically, the teaching context, deals with these issues, referring to the various forms of symbolic violence that we currently experience. In this way, appropriating a discursive perspective, that is, seeking to highlight how saying generates sense effects by being inscribed in history, affected by ideology, we seek to understand how the textbook behaves discursively in the approach to linguistic prejudice, identifying the rhetorical and linguistic strategies used to address this issue in the final years of elementary school. Based on these arguments, we raised the following research question: to what extent do the middle school textbooks particularized for analysis show themselves to be inscribed or not in discourses that tend to reinforce linguistic prejudice? For the development of the research, we set the following general objective: to analyze, discursively, aspects related to linguistic variety in textbooks aimed at middle school, tracing a parameter of analysis between the linguistic variants presented in these materials (prestige variants, standard norms, stigmatized variants) and the current scientific context's theoretical and methodological positions to observe, discursively, whether the ideology projected by them tends to reinforce or confront linguistic prejudice. The analyzes demonstrate that, despite seeking to discuss the issue of linguistic prejudice, inscribing themselves in innovative teaching discursive formations (TDI), mainly thematizing the issue of linguistic variety, the collections are, in large part, affected by an imaginary of traditional teaching discursive formations (FDT), reinforcing, to some extent, typical discourses of prejudiced positions. This implies that the analyzed collections seek to comply with the determinations of the official discourse on language teaching (FDO), which is crossed by both discursive perspectives, sometimes referring to innovative teaching, sometimes subjugating itself to notions of typically traditional teaching.